Avaliação das correlações existentes entre experiência de cárie, acúmulo de placa bacteriana e nível de Iga anti-streptococcus mutans na saliva de crianças com dentição mista - Mattos, Flávio de Freitas [UNESP] (2001)
This study aimed to evaluate the correlation between caries experience, plaque buildupandlevel ofIgAanti-Streptococcus mutansin salivaof children8-12years ofage,with mixed dentition. Withoutcaries(SC) lesions treated caries (CT) and untreated caries(CA), using the lHOSindex, ceod, ceos: 110 children, divided into three groups were examined.DMFT and DMFS.Samples were collected fromun stimulated saliva. The concentration of specific IgA was quantitated by ELISA to whole cell sof S. mutans. There was no significant correlation between the accumulation of plaque and salivary Ig Aspecific. There was a negative correlation between the level of specific salivary IgA and caries in the primary dentition of children with untreated caries lesions, indicating protective role. There was however,a positive correlation between the level of IgA and caries experiencein the permanent dentition of children with caries lesions treated. The salivary IgA specificanti-mutans does not prevent the buildup of plaque, with protective paperon the deciduous dentition and noton the permanent dentition